Oxygen - Dislocation interaction in zirconium from first principles. (15th June 2017) - Chaari, Nermine; Rodney, David; Clouet, Emmanuel
Abstract: Plasticity in zirconium alloys is mainly controlled by the interaction of 1 / 3 〈 1 2 ¯ 10 〉 screw dislocations with oxygen atoms in interstitial octahedral sites of the hexagonal close-packed lattice. This process is studied here using ab initio calculations based on the density functional theory. The atomic simulations show that a strong repulsion exists only when the O atoms lie in the dislocation core and belong to the prismatic dislocation habit plane. This is a consequence of the destruction of the octahedral sites by the stacking fault arising from the dislocation dissociation. Because of the repulsion, the dislocation partially cross-slips to an adjacent prismatic plane, in agreement with experiments where the lattice friction on screw dislocations in Zr-O alloys has been attributed to the presence of jogs on the dislocations due to local cross-slip. Graphical abstract: Image 1